2002
DOI: 10.1590/s1516-635x2002000200008
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Balance in Broiler Chicks During the First Week of Age

Abstract: Two experiments were carried out using 712 day-old chicks to evaluate the electrolytic balance (Na+K-Cl) in pre-starter (1-7 days) broiler diets. The feed, based on corn and soybean meal with 21.5 % protein and 2,900 kcal ME/kg, was offered ad libitum. In experiment I, K level was fixed, and Na and Cl levels were changed, using four 4 treatments and eight replicates of 16 birds. In experiment II, increasing levels of Na and K were used, with a total of four treatments and five repetitions of 10 birds. In both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Supplementation of varying DEB levels in drinking water did not affect litter moisture contents across several studies (Karunajeewa et al, 1986;Salvador et al, 1999) while other researchers (Balnave and Gorman, 1993;Nagwa and Maghraby, 1995;Borges et al, 2002) reported that this is directly related to DEB. Supplementation of varying DEB levels in drinking water did not affect litter moisture contents across several studies (Karunajeewa et al, 1986;Salvador et al, 1999) while other researchers (Balnave and Gorman, 1993;Nagwa and Maghraby, 1995;Borges et al, 2002) reported that this is directly related to DEB.…”
Section: Dietary Electrolytes Water Consumption and Litter Qualitymentioning
confidence: 89%
See 4 more Smart Citations
“…Supplementation of varying DEB levels in drinking water did not affect litter moisture contents across several studies (Karunajeewa et al, 1986;Salvador et al, 1999) while other researchers (Balnave and Gorman, 1993;Nagwa and Maghraby, 1995;Borges et al, 2002) reported that this is directly related to DEB. Supplementation of varying DEB levels in drinking water did not affect litter moisture contents across several studies (Karunajeewa et al, 1986;Salvador et al, 1999) while other researchers (Balnave and Gorman, 1993;Nagwa and Maghraby, 1995;Borges et al, 2002) reported that this is directly related to DEB.…”
Section: Dietary Electrolytes Water Consumption and Litter Qualitymentioning
confidence: 89%
“…Supplementation of varying DEB levels in drinking water did not affect litter moisture contents across several studies (Karunajeewa et al, 1986;Salvador et al, 1999) while other researchers (Balnave and Gorman, 1993;Nagwa and Maghraby, 1995;Borges et al, 2002) reported that this is directly related to DEB. Borges et al (2002) confirmed that there was no effect of DEB (246-277 mEq/kg) on the litter moisture. However, Maiorka et al (2004) did not find any effect of DEB (from 100 to 300 mEq) on excreta moisture up to seven days of age when DEB was changed using dietary Na.…”
Section: Dietary Electrolytes Water Consumption and Litter Qualitymentioning
confidence: 89%
See 3 more Smart Citations